STANDARDISATION OF RECIPE FOR THE PREPARATION OF LOBSTER ANALOGUES - Satam, S. B.; Joshi, V. R.; Desai, A. S. (Journal of Indian Fisheries Association, 2007)
Lobster analogues were prepared with lobster base flavour (paste), lobster cook water (whole lobster homogenate:water, 1:1 and 1:0.5) and lobster meat mince. In another experiment, different combinations of ginger-garlic paste and lobster base flavour, i.e., 1:3, 1:4, 1:6, 3:3, 3:4, 3:6, 5:3, 5:4 and 5:6 were added to the lobster analogue paste. It was observed that lobster analogues prepared with lobster base flavour (paste) are suitable organoleptically. The combination of ginger garlic paste and lobster base flavour in the ratio of 3:4 was found to be suitable organoleptically. Lobster analogues coloured with annatto seed colour at 1:2 (annatto seed:water) concentration had high values for the colour attribute as compared to orange-red synthetic colour, beetrootcolour, caramel colour and paprika colour. It was observed that come-up-time to achieve a temperature of850°C was 28 minutes with a processing period of 11 minutes.Keywords: Lobster analogues, surimi, colour, flavour